Metode Estimasi Massa Karbon Pohon Jeunjing (Paraserianthes falcataria L Nielsen) di Hutan Rakyat (Method for Estimation of Tree Carbon Mass of Paraserianthes falcataria L Nielsen in Community Forest) - Elias .; I Nyoman Jaya Wistara (Institut Pertanian Bogor (IPB University), 2009)
The study was conducted at Jalagajaya Village, Jasinga Subdistrict, Bogor District, West Java, Indonesia. The objective of the study was to apply a methodology and method for tree carbon mass stock estimation in community forest based on a field survey of the forest and a model of tree carbon mass equation. The study revealed that there was a difference on carbon content in the parts of the tree biomass. Based on the analysis, model of tree carbon mass equation of Paraserianthes falcataria L Nielsen at Julagajaya Village was C = 0.7D1.48, with R² adj. = 95.7%. Results of the tree carbon mass estimation of the Paraserianthes falcataria L Nielsen based on the tree carbon mass-equation model were lower than the results estimated based on the tree biomass-equation model of Brown (1997), but higher than the results estimated based on the tree biomass-equation model of Ketterings et al. (2001). The study showed that the tree carbon stock of the community forest Paraserianthes falcataria L Nielsen at Julagajaya Village in 1,2,3,4,5, and 6 year age stand were 29.262, 33.555, 36.041, 39.163, 33.163, and 56.943 ton ha-1, respectively.Keywords: biomass-equation model, tree carbon mass-equation model, tree carbon stock, communityforest